2015
DOI: 10.1097/cad.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

Transport of treosulfan and temozolomide across an in-vitro blood–brain barrier model

Abstract: In vitro, treosulfan (TREO) has shown high effectiveness against malignant gliomas. However, a first clinical trial for newly diagnosed glioblastoma did not show any positive effect. Even though dosing and timing might have been the reasons for this failure, it might also be that TREO does not reach the brain in sufficient amount. Surprisingly, there are no published data on TREO uptake into the brain of patients, despite extensive research on this compound. An in-vitro blood-brain barrier (BBB) model consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…However, the efflux ratio for TREO (1.88) did not reach the threshold for recognition of P-gp substrates, that is 2, and no concentration dependency of the drug distribution was observed. Therefore, involvement of the active efflux mechanisms in elimination of TREO from brain in vivo remains an open question (Linz et al, 2015). If that is the case, the higher brain exposure to TREO in the 10-day-old JR, in which the P-gp expression at BBB could be several times lower than in the 34-to 35-day-old YAR (Gazzin et al, 2008;Ose et al, 2008), is not surprising.…”
Section: Penetration Of Treosulfan and Its Monoepoxide Into Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efflux ratio for TREO (1.88) did not reach the threshold for recognition of P-gp substrates, that is 2, and no concentration dependency of the drug distribution was observed. Therefore, involvement of the active efflux mechanisms in elimination of TREO from brain in vivo remains an open question (Linz et al, 2015). If that is the case, the higher brain exposure to TREO in the 10-day-old JR, in which the P-gp expression at BBB could be several times lower than in the 34-to 35-day-old YAR (Gazzin et al, 2008;Ose et al, 2008), is not surprising.…”
Section: Penetration Of Treosulfan and Its Monoepoxide Into Cnsmentioning
confidence: 99%
“…In fact, all molecules enter from blood to CSF at a rate inversely related to molecular weight (MW), which explains why S,S-EBDM (MW 182 Da) penetrated into the rat CSF better than TREO (MW 278 Da) (Nau et al, 2010;Tam and Watts, 2010;Pardridge, 2012). As TREO may be a substrate for the efflux transporters, it is also worth mentioning that P-gp substrates, which cannot be found in appreciable concentrations in brain, typically penetrate into CSF (Linz et al, 2015).…”
Section: Penetration Of Treosulfan and Its Monoepoxide Into Cnsmentioning
confidence: 99%
“…Several studies provide data on the blood-brain transport of treosulfan and EBDM. In an in vitro study, Linz et al found that transport of treosulfan in the apical-to-basolateral direction (influx) is lower than the basolateral-to-apical (efflux), with permeability values of 1.6% and 3.0%, respectively [39]. The authors have also calculated a small logBB value (− 1.98), upon the ratio of treosulfan concentrations in brain and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon its hydrophilicity, TREO would not be predicted to readily cross the BBB and gain access to the CNS. In support of this claim, little penetrance of TREO and its active metabolites were detectable within the CNS of rats administered 500 mg/kg TREO, and limited amounts of TREO crossed an in vitro BBB model (20, 21). Virtually, all of the BMDCs detectable in TREO-conditioned mice had morphologies suggesting blood vessel-associated localizations (Table 1).…”
Section: Discussionmentioning
confidence: 88%
“…Treosulfan (TREO; Medac, DE), a hydrophilic analog of BU that does not readily cross the BBB (20, 21), was resuspended in sterile ddH 2 O at a concentration of 50 mg/mL just prior to administration. Doses were selected based upon previous studies by Van Pel et al and Nasa et al (22, 23).…”
Section: Methodsmentioning
confidence: 99%